Dasar Pertimbangan Penyidik Polres Magelang dalam Penentuan Alat Bukti Tindak Pidana Korupsi - Wardani, Rizki; Chrismonita, Verent Nadya; Damaika, Refia; Basri, Basri (Borobudur Law Review, 2019)
Corruption is an extraordinary crime that must be immediately eradicated because it is very detrimental to the state and impedes the development of the state. Corruption cases handled by law enforcers especially the police, are not easy. Corruption as one of the white collar crimes where the crime is committed by people who have positions and power is certainly not easy in the action of the crime, many interventions from various parties so that the action against corruption crime is stopped. This paper will discuss the basic considerations of Magelang Police Corruption Unit investigator in determining a minimum of pieces of evidence to be able to advance to the level of investigation. The research method used in this article is juridical normative namely in analyzing the problem carried out by combining legal materials (which secondary data) with primary data obtained in the field. From the results of the study it can be seen the principle investigators in the Magelang Police unit of Corruption with a minimum of 3 pieces of evidence to be able to advance to the investigation process aims to avoid the cessation of investigations (SP3) in the act of corruptions in Magelang.